TRANSLATING NON-EQUIVALENT VOCABULARY FROM UZBEK INTO ENGLISH IN LITERARY TEXTS: CULTURAL AND DIDACTIC APPROACHES (Ustozlar uchun, 2026)
This study examines the translation of non-equivalent vocabulary from Uzbek into English in literary contexts, focusing on cultural and didactic approaches that facilitate effective cross-linguistic communication. Non-equivalent vocabulary, particularly culture-specific items such as idioms, proverbs, and realia, presents significant challenges for translators due to the deep cultural embeddedness and lack of direct lexical correspondences between Uzbek and English. Through a qualitative-contrastive methodology, this research analyzes translation strategies employed in authentic literary texts, including works by prominent Uzbek authors such as Abdulla Qodiriy. The findings reveal that translators predominantly employ foreignization and domestication strategies, with varying degrees of success in preserving semantic, pragmatic, and cultural equivalence. The study proposes pedagogical implications for translation education, emphasizing the development of intercultural competence alongside linguistic proficiency. The research contributes to the growing body of knowledge on Turkic-English translation studies and offers practical insights for translators, educators, and language learners working with Central Asian literary texts.